How to elicit a negative bias? Manipulating contrast and saturation with the facial emotion salience task - Tholl, Sarah; Sojer, Christian A.; Schmidt, Stephanie N. L.; Mier, Daniela (Frontiers in Psychology, 2024)
Emotion recognition impairments and a tendency to misclassify neutral faces as negative are common in schizophrenia. A possible explanation for these deficits is aberrant salience attribution. To explore the possibility of salience driven emotion recognition deficits, we implemented novel facial emotion salience tasks (FESTs). Sixty-six healthy participants with variations in psychometric schizotypy completed the FESTs. In the FESTs, we manipulated physical salience (FEST-1: contrast, FEST-2: saturation) of emotionally salient (positive i.e., happy and negative i.e., fearful) and non-salient (neutral) facial expressions. When salience was high (increased contrast) , participants recognized negative facial expressions faster, whereas neutral faces were recognized more slowly and were more frequently misclassified as negative. When salience was low (decreased saturation), positive expressions were recognized more slowly. These measures were not associated with schizotypy in our sample. Our findings show that the match between physical and emotional salience influences emotion recognition and suggest that the FESTs are suitable to simulate aberrant salience processing during emotion recognition in healthy participants.